Theoretical Investigations on Deactivation of Copper Catalytic Species in Ullmann Cross Coupling Reactions - Gurjar, Kamlesh K.; Sharma, Rajendra K. (Asian Journal of Chemistry, 2018)
Copper mediated reactions require higher loading of copper salt and ligand. After few hours, copper active species becomes inactive and further loading of copper salt requires. Various hypothesis proposed in literature, were investigated. DFT studies were performed on more than 20 intermediate species. In present computational studies, it was found that ligation of carbonate base to active copper species is actual reason for deactivation. Carbonate and nucleophile are competitive ligand in these reactions.